The Effect of using the Technical Mathematics Lab on the Level of Achievement in Mathematics for the 37 th High School Students in Jeddah - Saudi Arabia - Al - Maghamsi, Fawzia Thuaiher Saleh (Arab Journal for Sciences and Research Publishing, 2016)
Objective: This study aims to investigate the effect of technical mathematics lab in teaching on the 37th secondary school students in Jeddah, Saudi Arabia. Methodology: The descriptive analytical method was used. The study included 28 female students from the 37th secondary school during the whole semester after using the technical mathematics lab. The sample of the study was randomly selected, the questionnaire was used as a tool for data collection, and the data was entered and analyzed by Microsoft software. Excel 2016. Results: The results showed that the technical mathematics lab has fun, thrill, cooperative participation and teamwork inside and outside the lesson 99%. In the The Technical Laboratory makes us a space to participate during the lesson 98%, which increases the understanding and achievement level 96%, and that students increased their chance of self-evaluation 97%. There were statistically significant differences in the mean scores of students between pre and post tests on the level of remembering, understanding, application and analysis. Abstract: The use of technical mathematics lab increased the thrill of cooperative participation and teamwork and improved understanding of mathematics and increased the level of academic achievement of students.
Keywords: technical laboratories; mathematics; secondary school; academic achievement